Unravelling differential Hes1 dynamics during axis elongation of mouse embryos through single-cell tracking - Azhar, Yasmine el; Schulthess, Pascal; van Oostrom, Marek J.; Weterings, Sonja D. C.; Meijer, Wilke H. M.; Tsuchida-Straeten, Nobuko; Thomas, Wouter M.; Bauer, Marianne; Sonnen, Katharina F. (Development, 2024)
The intricate dynamics of Hes expression across diverse cell types in the developing vertebrate embryonic tail have remained elusive. To address this, we have developed an endogenously tagged Hes1-Achilles mouse line, enabling precise quantification of dynamics at the single-cell resolution across various tissues. Our findings reveal striking disparities in Hes1 dynamics between presomitic mesoderm (PSM) and preneural tube (pre-NT) cells. While pre-NT cells display variable, low-amplitude oscillations, PSM cells exhibit synchronized, high-amplitude oscillations. Upon the induction of differentiation, the oscillation amplitude increases in pre-NT cells. Additionally, our study of Notch inhibition on Hes1 oscillations unveils distinct responses in PSM and pre-NT cells, corresponding to differential Notch ligand expression dynamics. These findings suggest the involvement of separate mechanisms driving Hes1 oscillations. Thus, Hes1 demonstrates dynamic behaviour across adjacent tissues of the embryonic tail, yet the varying oscillation parameters imply differences in the information that can be transmitted by these dynamics.
Online veröffentlicht: 26. September 2024
Gesehen am 26.03.2025